Successful treatment of fungal central thrombophlebitis by surgical thrombectomy in Korea: a case report - Eun Ji Lee; Jihoon T. Kim (Journal of Trauma and Injury)
Fungal thrombophlebitis of the central vein is a rare, life-threatening disease associated with significant morbidity and mortality. It requires immediate central venous catheter removal and intravenous antifungal therapy, combined in some cases with either anticoagulation or aggressive surgical debridement. A 70-year-old male patient injured by a falling object weighing 1,000 kg was transferred to our hospital. A contained rupture of the abdominal aorta with retroperitoneal hematoma was treated with primary aortic repair, and a small bowel perforation with mesenteric laceration was treated with resection and anastomosis. After a computed tomography scan, the patient was diagnosed with thrombophlebitis of the left internal jugular vein and brachiocephalic vein. Despite antifungal treatment, fever and candidemia persisted. Therefore, emergency debridement and thrombectomy were performed. After the operation, the patient was treated with an oral antifungal agent and direct oral anticoagulants. During a 1-year follow-up, no signs of candidemia relapse were observed. There is no optimal timing of surgical treatment for relapsed fungal central thrombophlebitis. Surgical treatment should be considered for early recovery.